Guidelines to Adapt Local Grocery Stores' TV Ads to Attract Native Spanish Speakers - Swanson, Robin; Garcia, Carlos G. (My University, 2017)
The purpose of this project was to develop guidelines to adapt local grocery stores' TV ads to focus on Spanish speakers.
Color poster with text, graphs, tables, and models.
Keywords: Grocery stores; Advertising; Spanish speakers; Posters